АҲМАД ДОНИШ САЁҲАТНОМАЛАРИНИНГ ЖАНРИЙ ХУСУСИЯТЛАРИ - Юнусзода, З.Ю. (SCIENCE and SOCIETY, 2016)
The article deals with the enlightenment of belles letters travel notes in the works of Ahmad Donish, turning into the genre, its fictional and real distinctive features.
Keywords: the travel notes; enlightenment; patriotism; national revive; realism; publicism